Buku Saku Pencegahan Stunting sebagai Alternatif Media dalam Meningkatkan Pengetahuan Ibu - Indah Purnama Sari; Inoy Trisnaini; Yustini Ardillah; Sulistiawati Sulistiawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Stunting is a chronic malnutrition problem that is caused by the lack of consumption of nutritious food in a long period of time, resulting in growth disorders in children, namely the length of the child is lower or shorter than the standard of age. Stunting on childrens has an impact on brain development disruption by delaying children's motor and cognitive development thereby reducing the quality of Indonesian human resources. The purpose of this activity was to increase the mother's nutritional knowledge in Seberang Ulu I District, Palembang through the provision and explanation of stunting pocket handbooks. The implementation of this activity was through home visits to every household that has a under two years. Knowledge test results showed a significant increase from pre-test and post-test means. This activites showed that the pocket handbook was effective in increasing mother's nutritional knowledge (p<0,05).